E-Skills and Digital Literacy: An Investigation into the Perceived Competencies of Distance Learning Students in the University of Lagos - Adewumi, Olusoji Olurotimi; Oladele, Esther Oluwasayo (NIU Journal of Humanities, 2023)
It is currently of utmost importance to ensure that students in higher education acquire and employ the digital literacy skills they will require to excel in their academic endeavours and personal lives. This research sought to find out students’ perceptions of their digital literacy and e-skills and the digital tools they utilise on a daily basis. The Distance Learners at the University of Lagos were randomly sampled (stratified) to respond to the researcher-designed questionnaires, to elicit responses from the learners. 354 respondents being female and 306 being males. A Cronbach alpha value of 0.78 was obtained. Analysis of the research questions show that there is a significant gap between the perceived importance of e-skills and digital literacy competencies and their actual usage. The findings suggest that there may be a need for greater focus on developing e-skills and digital literacy competencies among distance learning students. For instance, 64.4% of respondents use technology very frequently in their coursework. Institutions and educators may need to provide training and support to help students develop these skills. Additionally, students may need to prioritize their own learning of these skills and seek out resources and opportunities to develop themselves. However, the negative perceptions of a small percentage of respondents suggest that there may be areas where improvements could be made. Institutions and educators may need to continually evaluate their support programs to ensure they are meeting the needs of students, and work to address any areas where support may be lacking. Keywords: Digital Literacy, Perceived e-skills, Digital Information, Literacy Level, , e-Skills